Optimization of fractional composition of the excipient in the elastomeric covering for asphalt highways - E. M. Nurullaev; A. S. Ermilov (Fracture and Structural Integrity)
The computational method of optimum fractional composition of a dispersible filler of polymeric composite on the basis of three-dimensionally linked elastomer is developed according to non-linear programming. The coefficient of dynamic viscosity of polymeric suspension or the initial module of a viscoelasticity of the join solidification low-molecular rubbers with the final functional groups, filled by many fractional dioxide of silicon are considered as criteria of optimization. Influence of the limiting volume filling on energy of mechanical destruction was investigated. The elastomeric material is offered for use as a covering of asphalt highways in the form of a frost-proof waterproofing layer, which allowing multiply to increase operating properties.